Assessment of creep-fatigue behavior, deformation mechanisms, and microstructural evolution of alloy 709 under accelerated conditions. (July 2019) - Porter, T.D.; Findley, K.O.; Kaufman, M.J.; Wright, R.N.
Highlights: Alloy 709 fatigue life is reduced with the addition of a tensile hold time. Creep-fatigue life reduction is more significant at 550 °C compared to 650 °C. The cyclic stress response is correlated to microstructural evolution. Dynamic recovery results in lower tensile stresses and less grain boundary damage. A change in strain aging behavior results in a change of deformation behavior. Abstract: Alloy 709 is a leading candidate structural material for sodium-cooled fast spectrum reactors (FSR), where creep-fatigue is a potential failure mode. Low cycle fatigue (LCF) and creep-fatigue tests with 30 min tensile hold times have been conducted to failure at 550 and 650 °C, corresponding to potential service and accelerated test temperatures, respectively. Creep-fatigue life is reduced relative to LCF at both temperatures, though significantly more at 550 °C compared to 650 °C. Differences in slip behavior, dynamic recovery, precipitate evolution, and strain-aging effects result in less stress relaxation and sustained high tensile stresses in creep-fatigue at 550 °C; thus, there is more intergranular damage compared to 650 °C.